Impaired auditory evoked potentials and oscillations in frontal and auditory cortex of a schizophrenia mouse model - Shahriari, Yalda; Krusienski, Dean; Dadi, Yamini Sureka; Seo, Misun; Shin, Hee-Sup; Choi, Jee Hyun (TAYLOR & FRANCIS LTD, 2016)
Objectives: In patients with schizophrenia, -band (30-70Hz) auditory steady-state electroencephalogram responses (ASSR) are reduced in power and phase locking. Here, we examined whether -ASSR deficits are also present in a mouse model of schizophrenia, whose behavioural changes have shown schizophrenia-like endophenotypes. Methods: Electroencephalogram in frontal cortex and local field potential in primary auditory cortex were recorded in phospholipase C 1 (PLC-1) null mice during auditory binaural click trains at different rates (20-50Hz), and compared with wild-type littermates. Results: In mutant mice, the ASSR power was reduced at all tested rates. The phase locking in frontal cortex was reduced in the band (20Hz) but not in the band, whereas the phase locking in auditory cortex was reduced in the band. The cortico-cortical connectivity between frontal and auditory cortex was significantly reduced in mutant mice. Conclusions: The tested mouse model of schizophrenia showed impaired electrophysiological responses to auditory steady state stimulation, suggesting that it could be useful for preclinical studies of schizophrenia.
Keywords: GAMMA BAND OSCILLATIONS; PARVALBUMIN NEURONS; PREFRONTAL CORTEX; NMDA RECEPTOR; MICE; RESPONSES; BRAIN; PHOSPHOLIPASE-C-BETA-1; SYNCHRONIZATION; ENDOPHENOTYPES